Effects of replacement different levels of microbial protein for soya bean meal with two levels of calcium in the diet on Broiler performance. - J., Mohammed A.; A., Ahmed N.; Aljanabi, Thamer Kareem (Journal of Kerbala for Agricultural Sciences, 2017)
The present experiment was carried out by using one day unsexed 350 ASAFrench broiler chicks to study the effect of replacement different levels 0.0 , 5.0 , 7.5 , 10.0% of ethanol microbial protein for soya bean meal with two levels of calcium 1.25, 2.5 % in the ration, two replicates for each treatment, with 25 broiler chicks per replicate with suitable conditions in farm. The results revealed that no significant differences between treatments at 0-3 weeks (P < 0.05) in live body weight, feed consumption, and feed conversion ratio at 1.25% Ca level, however there were significant differences (P < 0.05) between the treatments at 2.5% Ca level in live body weight and feed conversion ratio. The results showed also that no significant differences between treatments for all broiler production parameters at 1.25% Ca level in 3-6 weeks, but there were significant differences (P < 0.05) in live body weight, feed conversion ratio at 2.5% Ca level. The results showed also that there were no significant differences in all production parameters investigated at 1.25% Ca level at 0-6 weeks but there were significant differences in live body weight and feed conversion ratio at 2.5% Ca level. No statistical differences between treatments in dressing percentage and liver weight of birds.